Harnessing Brewery Spent Grain for Polyhydroxyalkanoate Production - Robe D. Terfa; Priyanshi N. Patel; Hwidong D. Kim; Matthew D. Gacura; Gary Vanderlaan; Longyan Chen; Xiaoxu Ji; Davide Piovesan (Macromol)
The utility of brewery spent grain (BSG), a byproduct of the beer production process, for the synthesis of polyhydroxyalkanoates (PHAs), is a significant advancement towards sustainable and cost-effective biopolymer production. This paper reviews the upcycling potential of BSG as a substrate for PHA production, utilizing various biotechnological approaches to convert this abundant waste material into high-value biodegradable polymers. Through a comprehensive review of recent studies, we highlight the biochemical composition of BSG and its suitability for microbial fermentation processes. This research delves into different methodologies for PHA production from BSG, including the use of mixed microbial cultures (MMCs) for the synthesis of volatile fatty acids (VFAs), a critical precursor in PHA production, and solid-state fermentation (SSF) techniques. We also examine the optimization of process parameters such as pH, temperature, and microbial concentration through the application of the Doehlert design, revealing the intricate relationships between these factors and their impact on VFA profiles and PHA yields. Additionally, this paper discusses challenges and future perspectives for enhancing the efficiency and economic viability of PHA production from BSG. By harnessing the untapped potential of BSG, this research contributes to the development of a circular economy model, emphasizing waste valorization and the creation of sustainable alternatives to conventional plastics.